Prevention of hepatitis E: another step forward. (January 2011) - Goel, Amit; Aggarwal, Rakesh
Zhu F-C, Zhang J, Zhang X-F et al. : Efficacy and safety of a recombinant hepatitis E vaccine in healthy adults: a large-scale, randomised, double-blind placebo-controlled, Phase 3 trial. Lancet 376, 895–902 (2010). Hepatitis E virus (HEV) is frequently implicated in cases with acute viral hepatitis, particularly in developing countries. The infection, transmitted mainly by the fecal–oral route, is generally self-limited. A few affected individuals develop fulminant hepatic failure, a serious condition that is frequently fatal without liver transplantation. This outcome is particularly common when the infection occurs in pregnant women. A vaccine that contains a recombinant truncated capsid protein of HEV produced in an insect cell system has already been shown to be effective in preventing hepatitis E, at least in young men. However, it is not yet available on the market. In the evaluated article, Zhu et al. report the results of a large field trial of another vaccine against hepatitis E that contains a shorter part of the viral capsid protein, produced in Escherichia coli and adsorbed on alum. This trial, which included a large number of subjects of either gender aged 18–65 years, found this newer vaccine as safe and highly effective in preventing clinical disease caused by infection with HEV belonging to the genotype from which the vaccine was derived as well as another genotype. This study should prove to be a major stepping stone in our fight against this important disease pathogen.